APPLICATION OF LINEAR ALGEBRA IN DATA SCIENCE - Khayrullaev Temurbek Bobokhon o'g‘li; Yangiboyev Iftixor Dilmurod oʻgʻli; Khabibova Zarrina Ulugbekovna (Лучшие интеллектуальные исследования, 2024)
Annotation: In this article Application of linear algebra in data science, The purpose of science, the task of science, linear forms . Linear and square forms. Methods of making quadratic forms canonical. The law of inertia for the quadratic form. Information is given that they should have knowledge of positive definite quadratic forms .